A tunable Butterworth low-pass filter with digitally controlled DDCC - Y. S. Hwang (Radioengineering, 2013)
This paper presents a 6th-order tunable Butterworth low-pass active filter with Digitally Controlled Differential Difference Current Conveyor (DDCC). This active filter is synthesized using the systematic method of voltage-mode linear transformation (VMLT) which enables the filter use fewer active components, grounded capacitors and grounded resistors to avoid the parasitical effects. The bandwidth of the filter can be tuned by digital switches to adjust the output current of the DDCC. The specifications of the filter are based on 3G standard, and the filter is controlled by 8-bits digital signals. The tunable bandwidth of the filter is from 12 KHz to 2.6 MHz. The filter chip layout is realized by TSMC 0.18 um CMOS 1P6M mixed-mode technology. The supply voltage is 1.8V and the power consumption is 3.6 mW.